PENGARUH KONSENTRASI PUPUK HAYATI MAJEMUK DAN BATUAN FOSFAT ALAM TERHADAP SERAPAN P OLEH TANAMAN SELADA (Lactuca sativa L.) DI TANAH ANDISOLS - Joko Maryanto; - Abubakar (Universitas Trunojoyo Madura, 2010)
The aims of the experiment were to study the effect of Compound Biofertilizer (CB) and Rock Phosphate (RP) on the several soil chemistry properties of Andisols as well as the P-uptake by lettuce. The research had been conducted in the greenhouse of Agriculture Faculty, Unsoed at Karangreja, Purbalingga, since May up to August, 2009. The experiment was arranged in factorial 4 x 4 based on Completely Block Randomyzed Design with three replications. The firsrt factor was the concentration of CB consists of 4 levels, i.e. 0, 1, 2 and 3 %; and the second factor was the dosage of RP consists of 4 levels, i.e. 0; 25, 50 and 75 kg P2O5 per hectare. The variables observed were the soil pH, exchangeable aluminium, the availability of P, P-uptake by plant, plant height, number of leaf, fresh weight of plant and dry weight of plant. The data collected was analyzed using Fisher and DMR-test. The results indicated that the application of 75 kg P2O5 of RP could increase soil pH, reduce exchangeable-Al, increase the availability of P in the soil, P-uptake by plant, the fresh weight and dry weight of plant. The application of 2% concentration of CB could reduce exchangeable-Al, increase the availability of P in the soil, P-uptake by plant, the fresh weight and dry weight of plant.